Analysis of 161Tb by radiochemical separation and liquid scintillation counting. (April 2021) - Jiang, J.; Davies, A.; Arrigo, L.; Friese, J.; Seiner, B.N.; Greenwood, L.; Finch, Z.
Abstract: The determination of 161 Tb activity is problematic due to its very low fission yield, short half-life, and the complication of its gamma spectrum. At AWE, radiochemically purified 161 Tb solution was measured on a PerkinElmer 1220 Quantulus TM Liquid Scintillation Spectrometer. Since there was no 161 Tb certified standard solution available commercially, the counting efficiency was determined by the CIEMAT/NIST Efficiency Tracing method. The method was validated during a recent inter-laboratory comparison exercise involving the analysis of a uranium sample irradiated with thermal neutrons. The measured 161 Tb result was in excellent agreement with the result using gamma spectrometry and the result obtained by Pacific Northwest National Laboratory. Highlights: 161 Tb analysed by radiochemical separation and CNET LSC method. BEGe detector also used for activity measurement and radio-purity verification. Excellent agreement between results using CNET LSC, BEGe, and LEPS methods. Lower uncertainty and better detection limit achieved by CNET LSC.